2017
DOI: 10.14233/ajchem.2017.20810
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Liquid Chromatographic Method for Simultaneous Quantification of Naloxone and Oxycodone

Abstract: High performance liquid chromatography was applied to the simultaneous determination of naloxone and oxycodone. The method depends on separation and analysis of naloxone and oxycodone using C18 analytical column (250 × 4.6 mm, 5 µm). The mobile phase consists of a mixture of potassium dihydrogen phosphate (pH 5.5; 0.1 M) and acetonitrile (70:30, v/v). The photodiode array detector was set at 210 nm. The retention times of naloxone and oxycodone were 2.893 and 4.946 min, respectively. The total run time was 6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…38 There are many clinical studies have evaluated the efficacy of ketorolac or dexmedetomidine as adjuncts to oxycodone IV-PCA to provide superior pain relief, but still little or no information is available about the physical or chemical changes of these analgesic mixtures. 39 Therefore, it is suggested that the clinicians evaluate the compatibility and stability of the binary admixtures of opioid or non-opioid-oxycodone in future to ensure the safety and efficacy of oxycodone IV-PCA. 40 Of course this meta-analysis, the course of the paper had some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…38 There are many clinical studies have evaluated the efficacy of ketorolac or dexmedetomidine as adjuncts to oxycodone IV-PCA to provide superior pain relief, but still little or no information is available about the physical or chemical changes of these analgesic mixtures. 39 Therefore, it is suggested that the clinicians evaluate the compatibility and stability of the binary admixtures of opioid or non-opioid-oxycodone in future to ensure the safety and efficacy of oxycodone IV-PCA. 40 Of course this meta-analysis, the course of the paper had some limitations.…”
Section: Discussionmentioning
confidence: 99%